2002
DOI: 10.1159/000049414
|View full text |Cite
|
Sign up to set email alerts
|

Serial Assessment in Eclampsia of Cerebrohemodynamics by Combined Transcranial Doppler and Magnetic Resonance Angiography

Abstract: We used two different noninvasive methods, i.e., transcranial Doppler velocimetry and magnetic resonance angiography to serially assess cerebrohemodynamics in a patient with postpartum eclampsia. Five hours after an eclamptic seizure, a decrease in mean velocity in both middle cerebral arteries and slight angiographical spasms indicated cerebral hypoperfusion. On hospital day 8, the patient showed an increase in the mean velocity of the middle cerebral artery, accompanied by significant vasospasms. Abnormal fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Non-invasive MRA or CTA is preferred to conventional catheter-based angiography, and its associated complications, as RCVS tends to affect the circle of Willis or its immediate branches, which are adequately visualized with the former modalities. Alternatively, serial TCD ultrasound carried out over the course of one to two weeks may prove to demonstrate high specificity and sensitivity for RCVS and cerebral vasculitis, respectively (See Gomez et al, 1991& Ikeda et al, 2001). 70,71 Clearly, both the timing and the diagnostic performance of noninvasive vascular imaging and conventional angiography in this setting requires the performance of a prospective clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive MRA or CTA is preferred to conventional catheter-based angiography, and its associated complications, as RCVS tends to affect the circle of Willis or its immediate branches, which are adequately visualized with the former modalities. Alternatively, serial TCD ultrasound carried out over the course of one to two weeks may prove to demonstrate high specificity and sensitivity for RCVS and cerebral vasculitis, respectively (See Gomez et al, 1991& Ikeda et al, 2001). 70,71 Clearly, both the timing and the diagnostic performance of noninvasive vascular imaging and conventional angiography in this setting requires the performance of a prospective clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent prospective studies of recurrent TCH and RCVS, MCA was involved in all cases [11••,12••]. Alternatively, serial transcranial Doppler/transcranial color Doppler (TCD/TCCD) ultrasound carried out over the fi rst 2 months after presentation may prove to have high specifi city and sensitivity for RCVS and cerebral vasculitis, respectively [47,48]. A prospective study of RCVS with serial TCCD found that when subjects' maximum middle cerebral artery velocity (V MCA ) met "mild vasospasm criteria for SAH" (V MCA ≥ 120 cm/sec and a Lindegaard index [V MCA /V ICA , a ratio of middle cerebral to internal carotid artery velocity] score ≥ 3) patients had a greater risk of RPLS and ischemic strokes [12••].…”
Section: Pathophysiologymentioning
confidence: 99%
“…These changes in cerebral blood flow can cause cerebral ischemia and hemorrhage. 8,9 For these reasons, cesarean section is often used as the delivery mode in pregnancy with Moyamoya disease. However, we also use vaginal delivery with an epidural anesthesia to decrease cerebral blood flow.…”
Section: Introductionmentioning
confidence: 99%